The contingent valuation method in health care : - Nocera, Sandra (Kluwer Academic Publishers, 2003)
Talks about methodological aspects of the contingent valuation method. This work gives a holistic view of applying the contingent valuation method for use in policy. It shows the various stages of a contingent valuation study - design, the choice of elicitation techniques and estimation methods for willingness-to-pay and others